Corporate Communication and Organizational Performance: A Study in Commercial Banks in Kenya - Paul Muteti Kitemu; Anne Sang; Anita Wachira (Budapest International Research and Critics University, 2024)
The paper sought to assess the influence of corporate communication on organizational performance of commercial banks in Kenya. This was motivated by continued decline in the banking sector in the country, where despite the industry having over 39 licenced banks, only seven banks control over 70% of the market share. Moreover, the focus has mainly been emphasised on financial performance, which is only aligned to one section of stakeholders (shareholders) leaving behind other core stakeholders such as employees, customers, the community and regulators. Using a descriptive cross-sectional approach, the study collected data from 394 respondents drawn from the employees in the 39 commercial banks. A questionnaire was utilized, and the obtained data was analysed using SPSS. The findings revealed that corporate communication had a significant influence on organizational performance of commercial banks in Kenya (β = 0.526; P = 0.000<0.05). This implied that lack of effective communication during corporate change was significantly responsible for the decline in performance of the commercial banks. The study recommends the need for commercial banks through the senior management team that is responsible for corporate change, should integrate corporate communication as an essential tool to drive an holistic organizational performance where all the stakeholders’ needs are met. This will see more sustainable performance that can strengthen the banks’ growth and expansion.